Anti-Inflammatory Cytokine (IL-10) Profiles and Ratio of IL-6/IL-10 in Covid-19 Patients - Sari, Shinta Dewi Permata; Listiyaningsih, Erlin; Mawanti, Wening Tri; Martalena, Dewi (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: The number of COVID-19 cases in Indonesia has continually increased since the first cases appeared in March 2020. This disease is due to SARS-CoV-2 virus infection in the respiratory system that induces an immune response. The innate and adaptive immune response triggered the secretion of an excessive pro-inflammatory cytokine-caused cytokine storm that became one of the mechanisms of acute respiratory distress (ARDS). The anti-inflammatory cytokines (IL-10, IL-13, and IL-4) were secreted as the immune response in the ARDS condition. Purposes: This study aims to determine the ratio of the IL-6/IL-10 profile as basic information for the therapeutic approach to prevent ARDS. Methods: This cross-sectional study used stored biological material in plasma form from COVID-19 patients in Jakarta Islamic Hospital – Pondok Kopi and Dr. M. Goenawan Partowidigdo Hospital, Cisarua. The plasmas were from severe (n=20) patients and mild to moderate severity (n=25). The negative control sample was collected from 13 healthy subjects. Assessment of IL-10 levels in plasma using ELISA technique. Results: Our analysis showed that IL-10 has no statistical difference between negative control, mild to moderate, and severe categories (p=0.629). Meanwhile, the ratio IL-6/IL-10 presented statistical differences between mild to moderate and severe categories (p=0.011). The average ratio of IL-6/IL-10 in severe categories is two-fold higher than in mild-moderate categories. Conclusion: We conclude that there is a cytokine storm condition in severe COVID-19 patients with an imbalance ratio of pro-and anti-inflammatory cytokines and could be used as basic information for drug development in cytokine storm conditions to prevent ARDS.